Deconstructing homegardens: food sovereignty and development in northern Nicaragua - Boone, Karie, author; Taylor, Peter L., advisor; Fernandez-Gimenez, Maria E., committee member; Carolan, Michael S., committee member (Colorado State University. Libraries, 2012)
Through analysis of data from interviews, documents, and participant observation this study addresses the challenges and opportunities of homegardens as an effective strategy to promote food sovereignty and prepare for the projected negative climate change impacts. Why may farmers in the Segovias region of Nicaragua resist changing their food production and consumption strategies? This research examines the conceptualization of food sovereignty from the level of international food governance and highlights the disconnects that arise from NGO interventions. I suggest that promoting food sovereignty effectively will require concrete counter development strategies that lead NGOs to transform and democratize how they work.
Keywords: counter development; discourse; food security; food sovereignty; Nicaragua; sustainable agriculture